1988
DOI: 10.1093/nar/16.16.8186
|View full text |Cite
|
Sign up to set email alerts
|

A procedure forin vitroamplification of DNA segments that lie outside the boundaries of known sequences

Abstract: The polymerase chain reaction (PCR) system allows the amplification of DNA segments between two regions of known sequence [11. We describe a procedure that extends this technique to sequences that lie outside the boundaries of known sequences. The approach simply requires inversion of the sequence of interest by circularizaton and reopening at a different site. Figure 1 shows the procedure for amplifying segments (X and Z) in a genome, adjacent to a segment (Y-Y') of known sequence. The genome is first cleaved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
367
0
4

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 785 publications
(372 citation statements)
references
References 1 publication
1
367
0
4
Order By: Relevance
“…To determine the insertion site of the RNAi construct, we used an inverse PCR method [24,25]. Genomic DNA was isolated from 50 flies using a modification of the method described by Ballinger and Benzer [26].…”
Section: Ligase-mediated Inverse Pcrmentioning
confidence: 99%
“…To determine the insertion site of the RNAi construct, we used an inverse PCR method [24,25]. Genomic DNA was isolated from 50 flies using a modification of the method described by Ballinger and Benzer [26].…”
Section: Ligase-mediated Inverse Pcrmentioning
confidence: 99%
“…Inverse PCR (IPCR) was used to amplify DNA segments upstream of the known sequences as described by Triglia et al [17]. Briefly, this involved cutting genomic DNA with a restriction enzyme with sites outside and inside the known sequence, circularizing and then amplifying across the unknown region using PCR primers directed ' outwards ' from near the ends of the known sequence.…”
Section: Amplifying and Sequencing Of 5h E4 Sequencesmentioning
confidence: 99%
“…The genomic regions flanking the 'A' and 'B' tr-Dsloxs were isolated by IPCR (Triglia et al, 1988) and cloned into plasmids for sequence analysis. This analysis showed that the IPCR products were formed as predicted, with the expected restriction enzyme sites marking the junctions between Ds/ox sequence and unknown, genomic sequence.…”
Section: Characterization Of the 'A' And "B" Tr-dslox Insertionsmentioning
confidence: 99%